Hematopoietic Stem Cells Therapies - Chivu-Economescu, Mihaela; Rubach, Martin (Current Stem Cell Research & Therapy, 2017)
Stem cell-based therapies are recognized as a new way to treat various diseases and injuries, with a wide range of health benefits. The goal is to heal or replace diseased or destroyed organs or body parts with healthy new cells provided by stem cell transplantation. The current practical form of stem cell therapy is the hematopoietic stem cells transplant applied for the treatment of hematological disorders. There are over 2100 clinical studies in progress concerning hematopoietic stem cell therapies. All of them are using hematopoietic stem cells to treat various diseases like: cancers, leukemia, lymphoma, cardiac failure, neural disorders, auto-immune diseases, immunodeficiency, metabolic or genetic disorders. Several challenges are to be addressed prior to developing and applying large scale cell therapies: 1) to explain and control the mechanisms of differentiation and development toward a specific cell type needed to treat the disease, 2) to obtain a sufficient number of desired cell type for transplantation, 3) to overcome the immune rejection and 4) to show that transplanted cells fulfill their normal functions in vivo after transplants.
Keywords: Cell therapies